Superior strain-hardening and strength-ductility synergy by hierarchical L12 phases in a highly (Al, Ti)-added medium-entropy alloy - Shiyu Du; Tuanwei Zhang; Jinyao Ma; Zhiming Jiao; Jianjun Wang; Shengguo Ma; Renlong Xiong; Zhihua Wang (Journal of Materials Research and Technology)
A novel precipitate-strengthened Co–Cr–Ni medium-entropy alloy with a pure “FCC + L12” dual-phase structure is developed by adding a high concentration (6 at.%) of Al and Ti elements. After aging heat treatment at 700 °C for 4 h, the hierarchical L12 phases, composed of primary large-sized L12 phases (∼70 nm) and secondary L12 particles (∼14 nm), are achieved. The designed alloy featuring hierarchical L12 phases exhibits excellent strength-ductility combinations and strain-hardening ability, properties that are much improved over their counterparts with homogeneous dispersed L12 phases (∼13 nm) and without L12 phases. Especially, the yield strength (1320 MPa), ultimate tensile strength (1886 MPa), and average strain-hardening rate (5.15 GPa) are obtained in the alloy with hierarchical L12 precipitates deformed at cryogenic temperature. The Orowan bypass mechanism of the primary L12 phases, along with the shearing mechanism of the secondary L12 phases, collectively contributes to the exceptional strength of the alloy with hierarchical L12 precipitates. The penetration of dislocations and stacking faults (SFs) in the primary L12 phases, combined with hetero-deformation-induced (HDI) hardening attributed to these hierarchical L12 precipitates, may be a key factor in improving strain-hardening properties of the alloy.